2019
DOI: 10.1002/eat.23179
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic differences in the association between parent‐oriented perfectionism and disordered eating in college women

Abstract: Objective This study examined the associations between parent‐oriented dimensions of perfectionism (parental expectations [PE] and parental criticism [PC]) and eating disorder (ED) symptomatology across racial/ethnic groups. It was hypothesized that parent‐oriented perfectionism would be positively associated with ED symptomatology for White and Asian American women. Method Undergraduate women (N = 1,173) completed questionnaires assessing perfectionism, EDs, and demographics. One‐way analyses of variance test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 67 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…Moreover, the “Superwoman ideal” has been identified as an important correlate of eating psychopathology in other adolescent and young adult samples (Mensinger et al, 2007). Thus, clinicians should consider assessing perfectionism (both self- and socially-oriented) in SA Americans presenting for treatment (Goel et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the “Superwoman ideal” has been identified as an important correlate of eating psychopathology in other adolescent and young adult samples (Mensinger et al, 2007). Thus, clinicians should consider assessing perfectionism (both self- and socially-oriented) in SA Americans presenting for treatment (Goel et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Our sample was homogeneous (i.e., primarily non-Hispanic and white). Future research should focus on minority youth with AN and ARFID, given the dearth of research in this area, despite unique risk factors at play for these populations (Goel et al, 2019;Egbert et al, 2020Egbert et al, , 2022. Our sample size was modest (N = 91), which allowed us to detect only medium to large effect sizes.…”
Section: Including Age As a Covariatementioning
confidence: 99%
“…Multiple studies have demonstrated that Asians report higher levels of perfectionism than white people [ 48 , 80 , 81 ], which has been linked to authoritarian parenting styles and higher parental expectations in Asian families [ 15 , 82 ]. The findings of this systematic review conflicted with other Asian-American studies, which demonstrated a correlation between high parental expectations and disordered eating in participants [ 81 , 83 ]. However, a more recent study by Brosoft, Calebs and Levinson found that although perfectionism was higher in Asian-Americans, it was more strongly associated with ED symptoms in European-Americans [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that Asians report higher levels of perfectionism than white people [48,80,81], which has been linked to authoritarian parenting styles and higher parental expectations in Asian families [15,82]. The findings of this systematic review conflicted with other Asian-American studies, which demonstrated a correlation between high parental expectations and disordered eating in participants [81,83]. However, a more recent study by Brosoft, Calebs and Levinson found that although perfectionism was higher in Asian-Americans, it was more strongly associated with ED symptoms in European-Americans [80].…”
Section: Parental Expectationsmentioning
confidence: 99%